Estudos metabólicos, enzimáticos e genéticos do fungo endofítico Penicillium brasilianum - Fill, Taícia Pacheco (2014)
The project "Metabolic, enzymatic and genetic studies of the endophytic fungus P. brasilianum" resulted in biosynthetic studies of bisphenylpropanoid amides, the brasilimides, confirming the origin of these substances via phenylpropanoid biosynthesis pathway, very unusual in fungi. PAL activity, the first enzyme involved in this biosynthetic route was successfully evaluated and the conditions of PAL production by P. brasilianum were optimized (culture medium and induction of PAL adding Phe to the culture), and the incubation conditions of the enzymatic reaction. The specificity of the PAL enzyme was studied, and the enzyme showed activity toward all substrates tested, including acting as TAL (tyrosine ammonia lyase). In vivo studies throught the addition of different substrates lead to N-acetylation confirmed by spectroscopy data. The genome of the fungus P. brasilianum was sequenced, and extensive studies through bioinformatics lead to the gene encoding PAL enzyme. From molecular biology studies, the enzyme was cloned and expressed as recombinant PAL fused to a SUMO protein and a his-tag at the N- terminus of the protein in pETSUMO vector expressed in E. coli BL21 (DE3) to obtain the best conditions for enzyme overexpression in its soluble form. The purification process of the recombinant enzyme was studied from a single purification step (affinity chromatography) by pH gradient elution, obtaining a high degree of purity confirmed by one-dimensional electrophoresis. The pure recombinant PAL enzyme obtained was characterized by MS and biochemically yielding Km values of 4,8 mM. Recent studies seem to point out that there is a relationship between the production of brasiliamides when the fungus is subjected to stress conditions. The PAL enzyme appears to be involved in defense mechanisms in this fungus, as has been described for plants.